Endoscopic features of isolated and traditional serrated adenoma‐associated superficially serrated adenomas of the colorectum. Issue 1 (24th May 2021) - Mizuguchi, Yasuhiko; Tanaka, Yusaku; Cho, Hourin; Sekiguchi, Masau; Takamaru, Hiroyuki; Yamada, Masayoshi; Sakamoto, Taku; Matsuda, Takahisa; Hashimoto, Taiki; Sekine, Shigeki; Saito, Yutaka
Abstract : Background and Aim: Superficially serrated adenoma (SuSA) is a recently proposed subtype of colorectal serrated lesions. It is characterized by distinct clinicopathological and molecular features, including mixed serrated and adenomatous histology and frequent genetic alterations involving KRAS and RSPO . This study aimed to characterize the endoscopic features of isolated and traditional serrated adenoma (TSA)‐associated SuSAs. Methods: We retrospectively evaluated the endoscopic findings of 25 isolated SuSAs and 21 TSA‐associated SuSAs that were histologically and molecularly characterized. Results: SuSAs appeared as a sessile polyp or slightly elevated lesion located mostly in the sigmoid colon and rectum (88%). The size was between 3 and 20 mm (median, 6 mm). Most of them exhibited KRAS mutations (96%) and RSPO fusions/overexpression (92%). Endoscopically, many lesions had a whitish color (84%), a distinct border (96%), an irregular border (76%), and a lobulated surface (72%). However, diminutive lesions exhibited overlapping features with hyperplastic polyps. On narrow‐band imaging, vessel patterns were invisible or appeared as lacy microvessels in most lesions (80%). Chromoendoscopy invariably showed stellar or elongated/branched stellar pits, indicating a serrated microarchitecture. Most TSA‐associated SuSAs typically presented as polyps with a two‐tier raised appearance, consisting of whitish lower and reddish higher components corresponding to a SuSA and a TSA, respectively. Conclusions: SuSAs exhibit several characteristic endoscopic features on white‐light and image‐enhanced endoscopy. Diminutive lesions exhibit endoscopic features overlapping with hyperplastic polyps. Nonetheless, the endoscopic diagnosis of larger and TSA‐associated SuSAs may be feasible.